Áp dụng nghiệm pháp soi căn niệu sau vận động để phát hiện sớm sỏi thận - Đỗ, Đình Hồ (2011)
Tác giả: Đỗ Đình Hồ, GS,BS; Trần Thị Liên Minh, PGS,TS; Lê Xuân Trường, ThS; Đỗ Kim Hiền, BS -- Từ khóa: Sỏi thận; Sỏi đường tiết niệu